Commissioning and investigation of beam dynamics of phase I insertion devices at diamond - Singh, B; Bartolini, R; Fielder, R; Longhi, E; Martin, I; IEEE (2007)
Diamond is a 3 GeV low emittance third generation light source recently commissioned in Oxfordshire, UK. During Phase I of the project, seven insertion devices (IDs) have been installed and commissioned: these include 5 in-vacuum permanent magnet undulators, a variable polarization APPLE-II helical device (HU64) and a superconducting wiggler (SCW). We present our experiences commissioning these devices and the results of the investigations of their effects on beam dynamics, including orbit distortion, linear tune shifts, beta-beating and beam lifetime. Alpha-matching with local and global tune compensations, as well as the LOCO algorithm, have been used to compensate the linear optic perturbations. The results are discussed and compared with theoretical predictions. Injection with IDs in operation has also been investigated in view of future top-up operation.